2013
DOI: 10.1186/1475-2891-12-165
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycemic index, glycemic load and incidence of type 2 diabetes in Japanese men and women: the Japan public health center-based prospective study

Abstract: BackgroundJapanese diets contain a relatively high amount of carbohydrates, and its high dietary glycemic index and glycemic load may raise the risk of diabetes in the Japanese population. The current study evaluated the associations between the dietary glycemic index, glycemic load, and the risk of type 2 diabetes in a population based cohort in Japan.MethodsWe observed 27,769 men and 36,864 women (45–75 y) who participated in the second survey of the Japan Public Health Center-based Prospective Study. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
4
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 38 publications
8
55
4
8
Order By: Relevance
“…For example, the Nurses Health Study and Health Professionals Followup Study reported a non-significant direct association in women and inverse association in men for carbohydrate consumption and PD risk . In contrast, other studies have shown a positive association for total carbohydrate consumption and PD (Hellenbrand et al, 1996a;Abbott et al, 2003).High carbohydrate diets are associated with an increased risk of type 2 diabetes (T2DM) (Salmeron et al, 1997a,b;Oba et al, 2013). Interestingly, numerous epidemiological studies indicate T2DM is associated with an increased risk of PD Cereda et al, 2013) but the evidence presented is conflictive (Simon et al, 2007;Palacios et al, 2011;Noyce et al, 2012).…”
contrasting
confidence: 40%
See 2 more Smart Citations
“…For example, the Nurses Health Study and Health Professionals Followup Study reported a non-significant direct association in women and inverse association in men for carbohydrate consumption and PD risk . In contrast, other studies have shown a positive association for total carbohydrate consumption and PD (Hellenbrand et al, 1996a;Abbott et al, 2003).High carbohydrate diets are associated with an increased risk of type 2 diabetes (T2DM) (Salmeron et al, 1997a,b;Oba et al, 2013). Interestingly, numerous epidemiological studies indicate T2DM is associated with an increased risk of PD Cereda et al, 2013) but the evidence presented is conflictive (Simon et al, 2007;Palacios et al, 2011;Noyce et al, 2012).…”
contrasting
confidence: 40%
“…High carbohydrate diets are associated with an increased risk of type 2 diabetes (T2DM) (Salmeron et al, 1997a,b;Oba et al, 2013). Interestingly, numerous epidemiological studies indicate T2DM is associated with an increased risk of PD Cereda et al, 2013) but the evidence presented is conflictive (Simon et al, 2007;Palacios et al, 2011;Noyce et al, 2012).…”
Section: Carbohydratesmentioning
confidence: 83%
See 1 more Smart Citation
“…Diversos estudios han informado que los alimentos con elevados valores de IG y CG se han relacionado con un mayor riesgo de diabetes (11,12), pero otros reportes no han confirmado estos resultados. Como estrategia para ayudar a mantener la euglicemia en el diabético, existen suplementos nutricionales específicos para diabetes utilizados como sustitutos calóricos nutritivos en individuos normopesos, con sobrepeso u obesos; o suplementos para desnutridos con diabetes mellitus tipo 2 (DM2) (13).…”
Section: Introductionunclassified
“…Sin embargo, el consumo de grasas y proteínas no ha mostrado ninguna asociación (6,7). Otros estudios muestran que es la ingesta de CHO de alto índice glicémico la que incrementa el riesgo de DM2 (8).…”
Section: Introductionunclassified